Penerapan Manajemen Risiko Berdasarkan ISO 31000 pada UMKM Depot Air Minum Isi Ulang Afwin Cibiru Kota Bandung - Alma Aulia Siffa; Susi Nurohimah; Amira Muthi Ghassani; Maliha Rizka Humaira; Alfiana Alfiana (Indo Publishing, 2026)
This study aims to analyze the implementation of risk management based on ISO 31000 in the Afwin Cibiru refill drinking water depot, an MSME located in Bandung, Indonesia. Using a qualitative descriptive method through semi-structured interviews with the owner, the research identifies and evaluates risks related to market, finance, marketing, operations, human resources, and legal aspects. The risk mapping uses a risk matrix analysis to measure probability and impact levels for each event. The findings show that most risk events fall into medium and high categories, particularly risks associated with changing consumer preferences for fast delivery services, unstable operational costs, machine failures, hygiene violations, and dependence on a single worker. Applying ISO 31000 helps the business prioritize risk handling through preventive actions such as equipment maintenance schedules, hygiene control, financial recording, service expansion, and compliance with legal standards. The study concludes that structured risk management strengthens business continuity and improves operational efficiency for small-scale refill water depots.